An Examiner's Guide to Professional Plastic Surgery Exams - Klaassen, Michael F. (Springer Singapore, 2018)
This book serves as a guide for senior trainees preparing for their final professional exams at the end of at least 4 - 5 years of advanced training in an approved plastic and reconstructive surgery training programme. These exams are extremely challenging and difficult to pass, and a knowledge of plastic surgery alone is not enough. Judgement, discipline and the ability to handle the pressure of the exam interactions are key. The book dissects each segment of the exam and presents the common clinical, anatomical and pathological cases that candidates are likely to encounter.